Mewujudkan Kesejahteraan Melalui Dana Otonomi Khusus Aceh dalam Perspektif Hukum Keuangan Negara - Erlanda Juliansyah Putra (Universitas Syiah Kuala, 2014)
Special autonomy funds are regulated in Law Number 11 Year 2006 regarding the Government of Aceh basically provides a great opportunity for Aceh to improve the provision of public services and foster economic development in the region . Special autonomy fund is valid for a period of 20 ( twenty ) years , with details for the first year until the fifteenth year in the amount equivalent to 2 % ( two percent ) ceiling National General Allocation Fund and for the sixteenth to the twentieth year the amount equivalent to 1 % ( one percent ) of the National General Allocation Fund ceiling . That requires good financial management arrangements are based on the legal basis for the use of the budget in order to remain accountable for managing them for the sake of people's livelihoods. Creating the Welfare Through Special Autonomy Fund in Aceh in the Perspective of the State Finance Law